The Anxiety of PGSD’s Student In The Teaching of Mathemathics - Mahardika Darmawan Kusuma Wardana; Mohammad Faizal Amir (International Consortium of Education and Culture Research Studies, 2017)
Mathematics is a subject that has characteristics which different from other subjects. Mathematics subject mostly always splurging on numbers. This causes not all university students like this subject. Many university students are anxious when meeting or even more when teaching these subject. To find out more about the anxiety of students on mathematics, the researchers conducted a research to determine the anxiety that existed in the students while teaching mathematics subject. The method used in this research is qualitative, where in qualitative research is intended to explore the information that will be the basis of the design and detailed the specificity that exists in a unique context. The results of this study tells us if most PGSD student experience mathemathical anxiety when first teaching math.